Pengaruh Sales Growth, Profitabilitas, dan Leverage terhadap Tax Avoidance pada Perusahaan Pertambangan yang Terdaftar di Indeks Saham Syariah Indonesia (ISSI) - Dewi, Novita; Priyadi, Ira Hasti (Shafin: Sharia Finance and Accounting Journal, 2023)
Tax is a source of income for the state. However, on the other hand taxes can be a burden for a company. Sales growth is an increase in the number of sales of a company from one period to the next. With sales growth, companies can predict how much profit they will get. Profitability is the company's ability to earn profits through all the capabilities of its resources, such as the level of sales, capital, cash, number of employees and others. Leverage is a ratio that describes a company's ability to meet its long-term obligations. This means how much debt is borne by a company compared to its assets. Tax avoidance is an arrangement or way to minimize or eliminate the tax burden, and is not referred to as a tax violation because the taxpayer's efforts to reduce, avoid, minimize or alleviate the tax burden are still in a way that is allowed by the tax law. The data collection used in this study is using secondary data, namely by seeking information and collecting company financial reports through the website www.idx.com. The results of this study indicate that the Sales Growth and Profitability variables have a significant effect on Tax Avoidance, while the Leverage variable (DER) has no significant effect on Tax Avoidance.